A Prospective, Cohort Study of SITOIGANAP to Treat Glioblastoma When Given in Combination With Granulocyte-Macrophage Colony-Stimulating Factor/Cyclophosphamide/Bevacizumab/Nivolumab or Granulocyte-Macrophage Colony-Stimulating Factor/Cyclophosphamide/Bevacizumab/Pembrolizumab in Patients Who Failed Prior Treatment With Surgical Resection, Radiation, and Temozolomide - Bota, Daniela A.; Taylor, Thomas H.; Lomeli, Naomi; Kong, Xiao-Tang; Fu, Beverly D.; Schönthal, Axel H.; Singer, Samuel; Blumenthal, Deborah T.; Senecal, Frank M.; Linardou, Helena; Rokas, Evangelos; Antoniou, Dimitris G.; et al. (Frontiers in Oncology, 2022)
Introduction: Glioblastoma (GBM) is the most common primary, malignant brain tumor in adults and has a poor prognosis. Median progression-free survival of newly diagnosed GBM is approximately six months. The recurrence rate approaches 100 percent and the case-fatality ratio approaches one. Half the patients die within eight months of recurrence, and five-year survival is less than 10 percent. Advances in treatment options are urgently needed. We report on the efficacy and safety of a therapeutic vaccine (SITOIGANAP: Epitopoietic Research Corporation) administered to 21 patients with recurrent GBM (rGBM) under a Right-to-Try/Expanded Access program. SITOIGANAP is composed of both autologous and allogeneic tumor cells and lysates. Methods: Twenty-one patients with rGBM received SITOIGANAP on 28-day cycles in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF), cyclophosphamide, bevacizumab, and an anti-programmed cell death protein-1 (PD-1) monoclonal antibody (either nivolumab or pembrolizumab). Results: Median progression-free survival (mPFS) was 9.14 months and median overall survival (mOS) was 19.63 months from protocol entry. Currently, 14 patients (67%) are at least six months past their first SITOIGANAP cycle; 10 patients (48%) have received at least six cycles and have a mOS of 30.64 months, and 1-year survival of 90%. The enrollment and end-of-study CD3+/CD4+ T-lymphocyte counts strongly correlate with OS. Conclusions: The addition of SITOIGANAP/GM-CSF/cyclophosphamide to bevacizumab and an anti-programmed cell death protein-1 (PD-1) monoclonal antibody resulted in a significant survival benefit compared to historic control values in rGBM with minimal toxicity compared to current therapy.